PENGARUH PEMBERIAN Saccharomyces cerevisiae DAN Lactobacillus bulgaricus TERHADAP TITER ANTIBODI DAN PERTUMBUHAN PASCA VAKSINASI HOG CHOLERA PADA BABI - Nina Inocensia Welndy; Maxs U. E. Sanam; Yohanes T. R. M. R Simarmata (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2020)
Classical Swine Fever (CSF) or hog cholera caused by classical swine fever virus (CSFV) is an important infectious disease in domestic pigs and wild pigs because this disease has a high mortality and morbidity rate in susceptible livestock. One effective way to prevent the spread of hog cholera is to vaccinate at the age of 30 days or 43 days, which is the weaning age of pigs. Weaning age is a critical time in a production system because of disturbances in nutrition, the immune system and the physiological system. A probiotic diet such as Saccharomyces cerevisiae and Lactobacillus bulgaricus was done to minimize losses. This study aims to determine the response of antibody titres to hog cholera vaccination and to determine the growth rate of body weight among pigs after giving S. cerevisiae and L. bulgaricus as additional feed. The research sample of 27 pigs aged one month were divided into three groups, namely group A without giving probiotics as control, group B for pigs with S. cerevisiae yeast flour (50mg / kgBB) and group C for pigs with L fermentation. . bulgaricus (3ml / kgBW). Serum samples for ELISA test were collected on day 0 and day 21 after vaccination. There was no significant difference (P> 0.05) in the antibody response before and after vaccination between S. cerevisiae and L. bulgaricus supplemental feeding due to high maternal antibodies. Body weight growth after giving S. cerevisiae yeast flour showed a significant difference (P<0.05) at day 0 to day 14 and day 14 to day 28 but did not show a significant difference (P > 0.05).